CX3CR1 But Not CCR2 Expression Is Required for the Development of Autoimmune Peripheral Neuropathy in Mice - Oladiran, Oladayo; Shi, Xiang Qun; Fournier, Sylvie; Zhang, Ji (Frontiers in Immunology, 2021)
One hallmark of Guillain-Barre syndrome (GBS), a prototypic autoimmune peripheral neuropathy (APN) is infiltration of leukocytes (macrophages and T cells) into peripheral nerves, where chemokines and their receptors play major roles. In this study, we aimed to understand the potential contribution of chemokine receptors CCR2 and CX3CR1 in APN by using a well-established mouse model, B7.2 transgenic (L31) mice, which possesses a predisposed inflammatory background. We crossbred respectively CCR2KO and CX3CR1KO mice with L31 mice. The disease was initiated by partial ligation on one of the sciatic nerves. APN pathology and neurological function were evaluated on the other non-ligated sciatic nerve/limb. Our results revealed that L31/CX3CR1KO but not L31/CCR2KO mice were resistant to APN. CX3CR1 is needed for maintaining circulating monocyte and CD8+ T cell survival. While migration of a significant number of activated CD8+ T cells to peripheral nerves is essential in autoimmune response in nerve, recruitment of monocytes into PNS seems optional. Disease onset is independent of CCR2 mediated blood-derived macrophage recruitment, which can be replaced by compensatory proliferation of resident macrophages in peripheral nerve. CX3CR1 could also contribute to APN via its critical involvement in maintaining nerve macrophage phagocytic ability. We conclude that blockade of CX3CR1 signaling may represent an interesting anti-inflammatory strategy to improve therapeutic management for GBS patients.